2002
DOI: 10.1162/1054746021470577
|View full text |Cite
|
Sign up to set email alerts
|

Explorations in the Use of Augmented Reality for Geographic Visualization

Abstract: In this paper, we describe two explorations in the use of hybrid user interfaces for collaborative geographic data visualization. Our first interface combines three technologies: augmented reality (AR), immersive virtual reality (VR), and computer vision-based hand and object tracking. Wearing a lightweight display with an attached camera, users can look at a real map and see three-dimensional virtual terrain models overlaid on the map. From this AR interface, they can fly in and experience the model immersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 21 publications
(18 reference statements)
0
35
0
1
Order By: Relevance
“…The ARPRISM project investigated different interface technologies for viewing GIS data, including AR, VR, and hybrid technologies [6]. The main aim of the ARPRISM project was to investigate these technologies for face-to-face collaboration, and included a prototype interface designed to allow multiple users to view and interact with geospatial data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The ARPRISM project investigated different interface technologies for viewing GIS data, including AR, VR, and hybrid technologies [6]. The main aim of the ARPRISM project was to investigate these technologies for face-to-face collaboration, and included a prototype interface designed to allow multiple users to view and interact with geospatial data.…”
Section: Related Workmentioning
confidence: 99%
“…The requirement to support human-to-human interactions was demonstrated in Hedley et al [6]. Their informal trials with almost 100 users showed users liked the ability to see other each other in the physical world as well as in the AR model.…”
Section: Related Workmentioning
confidence: 99%
“…Portalés et al introduced a low-cost outdoor mobile AR application to integrate buildings of different urban spaces [5]. Hedley et al describe explorations in the use of AR for geographic visualization [6]. Du et al discuss key technologies of integrate outdoor AR with mobile Geographic information system (GIS) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to display some painting objects in the air, the augmented reality(AR) technique seems to be an effective technique, which overlay the virtual objects onto the real world by using a video or optical see-through device (1) . And, until now, some applications have been suggested that make multiple people intuitively share the complicated information in the real world, such as a map (2) or a scientific data (3) . In addition, it is not only a presentation technique of such information, and use for entertainment is also proposed, which multiple people enjoy to interact with a virtual character and the object together (4) .…”
Section: Introductionmentioning
confidence: 99%